Solution thermodynamics and preferential solvation of sulfamerazine in methanol+ water mixtures (2015)
The solubility of sulfamerazine (SMR) in methanol + water co-solvent mixtures was measured at five temperatures from 293.15 to 313.15 K. The mole fraction solubility of this sulfonamide was maximal in pure methanol